Impaired Decision Making and Loss of Inhibitory-Control in a Rat Model of Huntington Disease - El Massioui, Nicole; Lamirault, Charlotte; Yagüe, Sara; Adjeroud, Najia; Garces, Daniel; Maillard, Alexis; Tallot, Lucille; Yu-Taeger, Libo; Riess, Olaf; Allain, Philippe; Nguyen, Huu Phuc; von Hörsten, Stephan; et al. (Frontiers in Behavioral Neuroscience, 2016)
Cognitive deficits associated with Huntington disease (HD) are generally dominated by executive function disorders often associated with disinhibition and impulsivity/compulsivity. Few studies have directly examined symptoms and consequences of behavioral disinhibition in HD and its relation with decision-making. To assess the different forms of impulsivity in a transgenic model of HD (tgHD rats), two tasks assessing cognitive/choice impulsivity were used: risky decision-making with a Rat Gambling Task (RGT) and intertemporal choices with a delay discounting task (DD). To assess waiting or action impulsivity the differential reinforcement of low rate of responding task (DRL) was used. In parallel, the volume as well as cellular activity of the amygdala was analyzed. In contrast to WT rats, 15 months old tgHD rats exhibited a poor efficiency in the RGT task with difficulties to choose advantageous options, a steep delay discounting curve as delays increased in the DD task and a high rate of premature and bursts responses in the DRL task. tgHD rats also demonstrated a simultaneous and correlated presence of both action and cognitive/choice impulsivity in contrast to WT animals. Moreover, a reduced volume associated with an increased basal cellular activity of the central nucleus of amygdala indicated a dysfunctional amygdala in tgHD rats, which could underlie inhibitory dyscontrol. In conclusion, tgHD rats are a good model for impulsivity disorder that could be used more widely to identify potential pharmacotherapies to treat these invasive symptoms in HD.